LOM and HOM damping study in a superconducting deflecting cavity for ALS at LBNL - 施嘉儒 陈怀璧 唐传祥 郑曙昕 Derun Li (Chinese physics C, 2008)
Superconducting deflecting cavities can be used in synchrotron light source to generate subpicosecond X-ray pulses while the impedance of the lower order modes （LOM） and higher order modes （HOM） in the cavity should be kept below an accepted level to avoid beam instability. These modes can be damped by adding waveguide on beam pipe. Detailed simulation of Q in CST Microwave Studio is introduced and experiment results on an aluminum model cavity with damping waveguide are reported to make a comparison.